STUDI LITERASI : PELOPOR PEMBELAJARAN BERMAKNA MENGGUNAKAN TEKNOLOGI AUGMENTED REALITY PADA TOPIK LINGKUNGAN DI ERA MERDEKA BELAJAR - Devi Alvionita; Andi Basliahwanti Murti; Abdul Rasyid Fakhrun Gani (Bioilmi: Jurnal Pendidikan, 2021)
Responding to the challenges of education in the era of the industrial revolution 4.0, the use of technology has become a demand, including to facilitate the freedom of learning programs. Augmented reality is a technology product that is currently being popularly used in various fields including education. Augmented reality visual display in the form of three-dimensional images or animations can represent various abstract concepts that are not easy to learn. Augmented reality can be implemented in learning such as on environmental topics. This study aims to understand the role and use of technology in education, especially in the era of independent learning. This study uses a qualitative method with data collection through literature study. Learning using Augmented reality on environmental topics aims to provide understanding and various phenomena that occur in the environment are expected to have a positive influence on students. These positive influence includes changes in attitudes and behavior to become more concerned about the environment.